Efficacy and Safety of Levoketoconazole in Managing Cushing’s Syndrome: A Systematic Review - Shinjan Patra; Deep Dutta; Lakshmi Nagendra; Nishant Raizada (Indian Journal of Endocrinology and Metabolism, 2024)
No systematic review has holistically analysed the efficacy and safety of levoketoconazole, a novel purified 2S,4R enantiomer of ketoconazole, believed to be 15- to 25-fold more potent than ketoconazole for managing Cushing’s syndrome (CS). We undertook this meta-analysis to address this knowledge gap. Electronic databases were searched for studies involving patients with CS receiving levoketoconazole in the intervention arm. The primary outcome was to evaluate changes in mean 24-hour urine-free cortisol (mUFC) levels. Secondary outcomes were to evaluate alterations in cortisol and adverse events. SONICS study showed that normalisation of mUFC was seen in 61%, 55%, and 41% of the patients at the end of 6, 9, and 12 months therapy, respectively. The LOGICs study showed that withdrawal of levoketoconazole was associated with a significant increase in mUFC from 81.3 ± 35.7 to 220.8 ± 333.5 nmol/24h. The late-night salivary-cortisol (LNSC) increase during the drug withdrawal phase was 2.6 nmol/L in the placebo group (PG) compared to 2.2 nmol/L in the levoketoconazole group (LG) (P < 0.05). Re-initiation of levoketoconazole in original LG was associated with a decrease in mUFC from 224.3 ± 341.3 to 135.6 ± 87.3 nmol/24h. Initiation of levoketoconazole in the original PG was associated with a decrease in mUFC from 537.9 ± 346.0 to 141.3 ± 130.3 nmol/24h. Normalisation of mUFC was observed in 50.0% patients in LG compared to 4.5% in the placebo group. The median time for the response was 25 days. The median time to loss of therapeutic response was significantly shorter for PG (24 days) compared to LG (62 days) (P < 0.0001). Levoketoconazole has good efficacy and safety in CS. Bigger and longer studies are warranted to establish its superiority over ketoconazole.